2021
DOI: 10.1590/fm.2021.34102
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and its relationship with different anthropometric indicators in adults with obesity

Abstract: Abtract Introduction: Obesity compromises the quality of life. However, few studies have investigated the influence of different anthropometric indicators on the quality of life of this population. Objective: We aimed to correlate the physical and mental components of quality of life and verify its association with different anthropometric indicators in adults with obesity. Methods: A cross-sectional study was conducted in adults with obesity [body mass index (BMI) ≥ 30 kg/m²]. The quality of life was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…As measures or indicators of obesity, we observed that the WHtR, as well as the suprailiac and the subscapular skinfolds had the major correlations to HRQoL in both sexes (for boys, also body fat percentage; for girls, also waist circumference). An association between higher WHtR and poorer HRQoL among the adult population was previously reported (Tozetto et al, 2021). An increase in abdominal fat may be associated with decreased gene expression related to increased muscle mass maintenance which contributes to physical damage over time (Bonfante et al, 2017).…”
Section: Healthier Indexmentioning
confidence: 86%
“…As measures or indicators of obesity, we observed that the WHtR, as well as the suprailiac and the subscapular skinfolds had the major correlations to HRQoL in both sexes (for boys, also body fat percentage; for girls, also waist circumference). An association between higher WHtR and poorer HRQoL among the adult population was previously reported (Tozetto et al, 2021). An increase in abdominal fat may be associated with decreased gene expression related to increased muscle mass maintenance which contributes to physical damage over time (Bonfante et al, 2017).…”
Section: Healthier Indexmentioning
confidence: 86%